Evaluation of current symptoms in postoperative achilles tendons: a multimodal ultrasound study - Nunes, Priscila; Betsch, Marcel; Fuss, Bernhard; Dirrichs, Timm; Tingart, Markus; Quack, Valentin; Gatz, Matthias (Healthcare, 2021)
(1) Background: It is unknown which imaging parameters are associated with clinical persistent symptoms in postoperative Achilles tendons. This study used B-Mode, Power Doppler (PD-US), Ultrasound Tissue Characterization (UTC) and Shear Wave Elastography (SWE) to investigate which imaging parameters are associated with persistent symptoms in postoperative Achilles tendon tissue. (2) Methods: Retrospective, cross-sectional, multimodal imaging study. Based on the VISA-A score, postoperative tendons were assigned to two groups: 1. asymptomatic (VISA-A ≥ 90, n = 18); 2. symptomatic (VISA-A < 90, n = 10). The following imaging parameters were analyzed: UTC (echo type I, II, III, IV), B-Mode (diameter, cross sectional area, calcification, fiber irregularity), PD-US (Öhberg score) and SWE (SWE 3 mm, SWE area) using a t-test and a Mann-Whitney U test. (3) Results: SWE and PD-US showed significantly reduced elasticity and increased neovascularization in symptomatic tendons (SWE 3 mm p = 0.031, SWE area p = 0.046, Öhberg score p < 0.001). The only significant correlation between imaging parameters and the VISA-A score was assessed for SWE 3 mm (r = 0.378; p = 0.047) and the Öhberg score (r = −0.737; p < 0.001). Conclusions: Symptomatic postoperative Achilles tendons showed increased neovascularization and lower SWE values than asymptomatic ones. Future studies should examine the diagnostic accuracy of PD-US and SWE in detecting current symptoms in postoperative Achilles tendons.
Gesehen am 30.07.2021